DEVELOPING FLEXIBILITY IN 9–10-YEARS-OLD STUDENTS THROUGH GYMNASTICS TRAINING - Raxmatov Shoxrux; Xolboyeva Gulxayo (Research Focus International Scientific Journal, 2025)
This article discusses the importance and effectiveness of developing flexibility in 9-10-year-old students through gymnastics exercises. The article describes appropriate exercises, techniques, and methods for enhancing flexibility. It also analyzes the impact of flexibility development on body shape and overall physical health. This scientific paper helps establish clear guidelines for physical education in students.